Block of an electron gun combined with a getter - ion pump designed for high - power beam - plasma microwave devices - Antonov, A.N.; Yegorov, A.M.; Kovpik, O.F.; Kornilov, E.A.; Svichensky, V.G. (Вопросы атомной науки и техники, 2008)
The paper presents the design description and the results of tests of the block combining an electron gun and a getter - ion pump, providing plasma - forming gas evacuation from the slow - wave structures. The block is designed for use in high-power beam - plasma devices. The construction under consideration minimizes the overall block dimensions. The block, in the assembly of the generator with a hybrid slow-wave structure (a sequence of inductively coupled resonators and a plasma - filled transport channel) provides the generation of stochastic oscillations in the tenth-centimeter wavelength range in the frequency band of 1 GHz, 40 kW microwave power in the continuous mode of operation and 100 kW in the pulse of 4 ms duration.